Transcatheter ventilation with a modified Rapid-O2 oxygen insufflation device - Jaewon Jang; Hye Jin Kim; Hyun Joo Kim; Wyun Kon Park (Korean Journal of Anesthesiology)
Background The Rapid-O2 oxygen insufflation device® (Rapid-O2) was designed primarily for rescue oxygenation in cannot intubate, cannot oxygenate (CICO) events; thus, hypercapnia is inevitable. Rapid-O2 was modified to enhance ventilation using the Venturi effect during expiration. Methods To determine the most effective combination of inner catheters (20 gauge [G], 18 G, 16 G, 14 G, and 2-mm inner diameter [ID] transtracheal catheter [TTC]) and insufflation catheters (16 G, 14 G, and 2-mm ID TTC) for achieving optimum ventilation, insufflating and expiratory flows were measured at an oxygen flow rate of 15 L/min. The insufflating and expiratory pressures were measured at 6–15 L/min. The flows and pressures were measured using a gas flow analyzer. The insufflating and expiratory times were measured using a trachea-lung model to obtain minute volumes. To assess the improvement by modifying the Rapid-O2, minute volumes were measured using the Rapid-O2. Results The most appropriate inner catheter was 18 G. The insufflating pressures ranged from 97 (2-mm ID TTC) to 377 cmH2O (16 G) at 15 L/min. During expiration, similar negative pressures of 50 cmH2O were measured in the insufflation catheters at 15 L/min. At lung compliance of 100 ml/cmH2O, the minute volumes through a 2-mm ID and 14 G insufflation catheters were 7.0 and 5.37 L/min, respectively, at 15 L/min. The minute volumes were significantly greater in modified Rapid-O2. Conclusions Modified Rapid-O2 provided sufficient minute volumes in adults using a 14 G or 2-mm ID insufflation catheter at 15 L/min, demonstrating its potential for ventilation in CICO events.